Gali Lubang Tutup Lubang di Tengah Pandemi: Teknologi Finansial dalam Perspektif Hukum dan Teori Keamanan - Marwan, Awaludin; Ashghor, Aly (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2020)
Financial technology gives easy and fast access to society in financial services, especially the fintech lending sector. Unfortunately, some problems appear in the field. For instance, the lack of financial literacy which cases the difficulty of society to fulfill their right and duty. The absence of financial literacy has also caused the phenomenon of ‘making hole, closing hole,’ in which the pandemic situation this phenomena is getting bigger. Meanwhile the existence of illegal fintech which conducted to crawl data privacy, extortion, and terror. From a law and security theory perspective, this case can become an object for further study. By using normative and socio-legal approach, this research tries to analyze the implementation of fintech lending regulation. The main stakeholder, such as the Financial Service Authority (OJK) makes some efforts to amend the new regulation to improve the current regulation. The industry association also works out to establish the Fintech Data Center (FDC) to minimize the problems.